Enigmatic epistemic things: The epistemic role of artworks in artistic research doctorates - Solberg, Anne (FormAkademisk, 2020)
The aim of this article is to discuss epistemology, focusing on the epistemic role of artwork in research projects. Porcelaneous is the initial phase of a three-year artistic research project with an artistic component comprising the making of porcelain boards. The porcelain boards and the making process in this initial phase are used as examples from practice. At the core of the epistemological discussion is Hans-Jörg Rheinberger’s theory on experimental systems and epistemic things. Rheinberger advocates for an objective and practice-oriented approach rather than a theoretical approach to experimental research. In his setting, epistemic things are material. This article has concluded that Rheinberger’s theory is about attitudes rather than research methods and that this attitude to epistemological questions is relevant for artistic research.